PENGARUH KONSENTRASI PVP K - 30 SEBAGAI BAHAN PENGIKAT TERHADAP MUTU FISIK TABLET EKSTRAK DAUN TEKELAN (Chromolaena Odorata. (L.) - Ariyani Buang (Jurnal Kesehatan Yamasi Makassar, 2022)
The Tekelan leaves (Chromolaena odorata (L) contain chemical compounds in the form of phenolics, steroids, terpenoids and alkaloids, flavonoids that have anti-inflammatory and antioxidant activity. Tekelan leaves are made into tablet dosage form because they have the advantage of being easy to consume, practical, has the right dosage, and the stability still protected in storage.The purpose of this study is to determine the effect of variations in the concentration of PVP K-30 as a binder on the physical quality of Tekelan leaf extract tablets (Chromolaena odorata (L) and to determine the concentration of PVP K-30 which produced Tekelan leaf extract tablets (Chromolaena odorata (L). with physical quality This study is being held in the Pharmacy Technology Laboratory of the Health Ministry of Health, Makassar. The Tekelan leaves were extracted by maceration using 96% ethanol as solvent. The Tekelan leaf extract with a dose of 56 mg was formulated into tablet dosage form using variations in the concentration of PVP K-30, namely F1 :1% w/v, F2 :3% w/v and F3 :5% w/v, then the physical quality of granul is tested which included air content testing, angle of repose test, real specific gravity test, compression density test, compressibility test, and flow rate test then continued with the physical test tablets including tablet size uniformity test, tablet weight uniformity test, hardness test, friability test, and disintegration time test. The results of research obtained that the physical quality of the granules meets the requirements of a good granule. For testing the physical quality of tablets, it was found that PVP K-30 at a concentration of 5% produced Tekelan leaf extract tablets with the best physical quality.